Climatic characterization of heavy precipitation events in Madeira island - Couto, Flavio (2020)
This work aims to discuss two climatic factors producing heavy precipitation events in Madeira Island. In general, several socio-economical damages due heavy precipitation can be reported in many regions worldwide. In order to identify such factors, this work has been based on previous studies carried out after the disaster on 20 February 2010, which presented different approaches about the subject. Under a mesoscale context, the local effects are investigated from very-high horizontal resolution simulations performed with the Meso-NH model. On a large scale, the features associated with the precipitable water field over the Equatorial and Subtropical Atlantic Ocean are explored from satellite observations. Two factors determining heavy precipitation events in the island have been highlighted. The first one, related to the local complex orography, whereas the second one was associated with the large scale circulation, namely the meridional water vapour transport affecting the island.